Estimating the Shutdown Effect of the Old Coal-fired Power Plants on PM2.5 and its Composition - Bae, Minah; Kim, Soontae; Yoo, Cheol (Journal of Korean Society for Atmospheric Environment, 2020)
We estimated the shutdown impact of the old coal-fired power plants on PM2.5 concentration over Chungnam and South Korea for the period of March~September 2017. The impact was estimated by the brute force approach in which the entire emissions of the target old coal-fired power plants were zero out. Three-dimensional chemistry transport model, Community Multiscale Air Quality (CMAQ), was used for the base and sensitivity simulations. The shutdown of the power plants has decreased PM2.5 levels in South Korea and Chungnam by 0.1 μg/m3 and 0.23 μg/m3, respectively during the period. Note that the NOx and SO2 emissions from the old coal-fired power plants take only ~2% of the total domestic emissions, and thus PM2.5 concentration can be reduced even further when more stringent NOx and SO2 controls become enforced. Relative impacts of sulfate and nitrate show apparent monthly variations, possibly due to changes in meteorological factors affecting the secondary aerosol formation. For example, the impact of nitrate remained high during cold months while that of sulfate increased in summer (July~August). From this result, even if the fuel of a power plant has changed from coal to eco-friendly fuel such as LNG, it is difficult to expect the nitrate decrease without NOx emission reduction. On the other hand, the impact of the old coal-fired power plants has increased by up to 8 times when ammonia emissions from the Selective Catalytic Reduction/Selective Non-Catalytic Reduction (SCR/SNCR) in the facilities are considered. Therefore, it is essential to provide accurate precursor emissions including ammonia slipped from the emission control device to evaluate their overall impacts on the air quality.
Keywords: Coal-fired power plant; Nitrate; PM2.5; Shutdown Impact; Sulfate